Grupos consonánticos cultos en el siglo XVI y XVII: ¿representación fonémica o norma gráfica? - Arias, Beatriz (2008)
This paper examines the graphic representation of some consonant groups considered educated in the colonial Mexican Spanish in documents, charts and orthographies from XVI and XVII centuries. As of this work, it has been possible the registration of some different types of graphic representations for the consonants in implosive position, they are similar to the ones registered in the popular language of this zone. This research offers two striking points. On one side, it demonstrates that the graphic study of novo-Hispanic documents provides clues about the “realization” of the educated groups from the period under scrutiny. On the other hand, I conclude that many of these phenomena occur in the outlines of the syllable, specifically in the coda, and that they are very similar to those found in the popular speech of Mexicans from the XXI.